The risk aáeáment index in grape powdery mildew control decisions and the effect of temperature and humidity on conidial germination of Erysiphe necator - Bendek, C.E.=700 1 Campbell, P.A.; Torres, R.; Donoso, A.; Latorre, B.A.
Es, En)
Ilus., 33 ref.
Keywords: VITIS VINIFERA; ENFERMEDADES DE LAS PLANTAS; UNCINULA; DIAGNOSTICO; TEMPERATURA; HUMEDAD RELATIVA; CHILE